Report on professional attachment with Y. M. Woo & Co. - Tan, Donald Eng Hock (2015)
This report highlights the lessons and experiences I have gained during the professional attachment, not only practical auditing and computer skills, but also important human skills that are required of a professional auditor. These experiences have been obtained either through actual audits I have done or through one-to-one discussion sessions I had with my audit supervisor. It is hoped that with the material and format presented, I can sufficiently share my experiences with the reader.